2021
DOI: 10.1002/sce.21680
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging curricular and students' resources to instigate and sustain problematizing

Abstract: Although existing literature suggests that teachers perceive, mobilize, and leverage resources to support ambitious instruction, less is known about how teachers and students jointly take up resources for co-constructing scientific knowledge. This study examines how teachersThere is a rich body of scholarship in educational policy, mathematics, and most recently, science education that has examined how teachers utilize resources to support and sustain ambitious instruction. Resources are the set of social, mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Sometimes, what is uncertain for an individual might not be productive for a classroom community to engage with at that time, leaving teachers to grapple with how much to attend to individuals' uncertainty as compared to the class's sense‐making (Colley & Windschitl, 2016). Furthermore, what is uncertain for students is likely to be at least somewhat settled by scientists and/or might not be a conceptual target for instruction (Ko, 2021; Manz & Suárez, 2018). Alternatively, students might not have sufficient resources to articulate a clear problem or make progress on it.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Sometimes, what is uncertain for an individual might not be productive for a classroom community to engage with at that time, leaving teachers to grapple with how much to attend to individuals' uncertainty as compared to the class's sense‐making (Colley & Windschitl, 2016). Furthermore, what is uncertain for students is likely to be at least somewhat settled by scientists and/or might not be a conceptual target for instruction (Ko, 2021; Manz & Suárez, 2018). Alternatively, students might not have sufficient resources to articulate a clear problem or make progress on it.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Therefore, a classroom community's science work can be understood as being convergent on, or divergent from, the planned curricular trajectory. By extension, teachers need the capacity to “open up” curricular materials to localize students' convergent science work and pursue their divergent science work (Ko, 2021; Ko & Krist, 2019). Taken together, this view of science work in curricular enactment provides a useful lens into how students act with epistemic agency in the context of curricular enactment.…”
Section: Discussionmentioning
confidence: 99%
“…Science teachers can draw on the planned trajectory of the curriculum to design and enact instruction for students' to act with epistemic agency (Ko, 2021; Ko & Krist, 2019). However, curricular enactments for epistemic agency require adaptation and improvisation of the materials (Drake, 2002; Heaton, 2000; Lampert, 1986).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, connecting the scientific inquiry with the everyday forms of relating to the world could allow the students to students engage in doing science in ways that are meaningful in their everyday lives (cf. Kervinen et al, 2020b;Ko, 2021).…”
Section: Envisioning Alternative Scenarios and Narrativesmentioning
confidence: 99%
“…The findings of this study also show how students reframed the uncertainty through the integration of their everyday experience in the inquiry processes. Integration of everyday forms of knowing in science teaching is essential to make it meaningful for the students (e.g., Archer et al, 2010;Ko, 2021), and it has been shown that the absence of a teacher in particular can enable such connections particularly well (Kervinen et al, 2020b). The present study extends the previous work by showing how the students used their everyday experiences and understandings of urban life as a resource to manage uncertainty that is meaningful not only for themselves but also regarding the production of new knowledge of the world.…”
Section: Students Reframe Uncertaintymentioning
confidence: 99%